Crossover gait in running and measuring foot inversion angle at initial foot strike: a front-view video analysis approach - Iskandar, Muhammad Nur Shahril; Loh, Ray Ban Chuan; Ho, Mee Yee Mavis; Pan, Jing Wen; Kong, Pui Wah (Frontiers in Bioengineering and Biotechnology, 2023)
Foot inversion angle at initial foot strike is associated with various running-related injuries. Traditionally, video analysis of foot inversion angle has been accomplished by positioning a camera to record from the back view, but complications arise when a crossover gait obscures the area of measurement. This study aims to investigate the viability of measuring foot inversion angles at initial foot strike of running from the front view as an alternative to using the back view in 2D video analysis. Forty-four healthy runners (20 females, 24 males) ran at their self-selected speeds on a treadmill with their gait recorded from front and back camera views. Foot inversion angles at initial foot strike were analyzed using Kinovea. A 2 × 2 (Camera × Foot) ANOVA with repeated measures was performed on the foot inversion angle data. Subsequently, correlation and linear regression were performed to determine the relationship between the back and front-view measurements. Thirteen runners (29.5%) displayed crossover gait within 18 gait cycles. ANOVA revealed a significant main effect on Camera (p < .001) only, where foot inversion angle was greater from the front camera view. Correlation analysis showed a significant positive correlation between the front and back camera views (r = 0.388, p < .001). Regression analyses yielded an equation, 𝑦𝑦 = 0.42 + 0.53𝑥𝑥, where 𝑦𝑦 and 𝑥𝑥 were the foot inversion angle measured from the back and front camera views, respectively. With a linear regression conversion equation, front-view foot inversion angles at initial foot strike can be used to determine rearfoot inversion angles when crossover gait obstructs the back camera view.